Lung-targeting lentiviral vector for passive immunisation against influenza. Issue 12 (3rd September 2020) - Tan, Tiong Kit; Gamlen, Toby P E; Rijal, Pramila; Townsend, Alain R; Gill, Deborah R; Hyde, Stephen C
Abstract : When recombinant simian immunodeficiency virus (SIV) is pseudotyped with the F and HN glycoproteins from murine respiratory Sendai virus (rSIV.F/HN), it provides efficient lung cell targeting and lifelong transgene expression in the murine airways. We have shown that a single dose of rSIV.F/HN can direct stable expression of neutralising antibody against influenza in the murine airways and systemic circulation, and protects mice against two different influenza strains in lethal challenge experiments. These data suggest that rSIV.F/HN could be used as a vector for passive immunisation against influenza and other respiratory pathogens.